2019
DOI: 10.1186/s13256-019-2273-7
|View full text |Cite
|
Sign up to set email alerts
|

A pediatric cancer patient with suspected chemical coping following high-dose opioid therapy: a case report

Abstract: BackgroundChemical coping is an inappropriate method for dealing with stress through the use of opioids; it is considered the stage prior to abuse and dependence. In patients with cancer, it is important to evaluate the risk of chemical coping when using opioids. There are some pediatric opioid use-related tolerances and addictions; however, no mention of chemical coping has been found.Case presentationWe present a case of an 11-year-old Japanese boy with acute lymphocytic leukemia. After transplantation, he c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…A search of the literature by the authors found only 3 additional case studies demonstrating a similar phenomenon: an 11-year-old boy with presumed graft-versus-host disease which was later demonstrated to be chemical coping titrated to high doses on fentanyl (max dose = 9720–10,908 morphine equivalent daily dose) 3 ; a 40-year-old woman prescribed oxycodone postoperatively on an escalating dose (max dose = 16,500 morphine equivalent daily dose) 4 ; and a 59-year-old man who was using his palliative wife's transmucosal fentanyl (max dose = 11,520–12,928 morphine equivalent daily dose) 5 . We are not able to calculate NC's morphine equivalents due to her methadone and its dose equivalency being poorly established 6 .…”
Section: Discussionmentioning
confidence: 99%
“…A search of the literature by the authors found only 3 additional case studies demonstrating a similar phenomenon: an 11-year-old boy with presumed graft-versus-host disease which was later demonstrated to be chemical coping titrated to high doses on fentanyl (max dose = 9720–10,908 morphine equivalent daily dose) 3 ; a 40-year-old woman prescribed oxycodone postoperatively on an escalating dose (max dose = 16,500 morphine equivalent daily dose) 4 ; and a 59-year-old man who was using his palliative wife's transmucosal fentanyl (max dose = 11,520–12,928 morphine equivalent daily dose) 5 . We are not able to calculate NC's morphine equivalents due to her methadone and its dose equivalency being poorly established 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Miura et al and Rodriguez-Mayoral et al reported cases of patients who received antidepressants alone to treat cancer-related anxiety [7,8]. The most important point of these cases is that for relatively young patients, antidepressants alone appear to be effective against anxiety caused by cancer.…”
Section: Discussionmentioning
confidence: 99%